BAURAN PEMASARAN DAN KINERJA USAHA INDUSTRI KECIL ROTI DI BANDAR LAMPUNG - Han Prahara Lukyta; Wuryaningsih Dwi Sayekti; Suriaty Situmorang (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2020)
This research aims to explore the perception of bread micro industry enterpreneurs about the marketing mix, the performance of bread micro industry, and the influence of the the perception on the performance. The research was conducted in Bandar Lampung using a survey method. The research location was selected purposively because Bandar Lampung city is one of the potential areas to developing bread micro industries. Data of this research were collected in. December 2016. The results showed that enterpreneurs’ perceptions on marketing mixes, in terms of product, price, and promotion mixes are included in important category, while perception in place mix is included in important enough category. Based on the values of return on investment, profit margin, and operation ratio, the micro bakery industries in Bandar Lampung have been included in very good category. The enterpreneurs’ perception on price mix influences the performance of micro bakery industry, while the other mixes do not influence the performance.Key words: bread, marketing mix, micro industry, performance